Anti-Smoking Media Campaigns and Disparities in Smoking Cessation in the United States, 2001-2015. Issue 5 (June 2021) - Colston, David C.; Cho, Beomyoung; Thrasher, James F.; Titus, Andrea R.; Xie, Yanmei; Emery, Sherry; Elliott, Michael R.; Fleischer, Nancy L.
Purpose: To evaluate sociodemographic differences in the relationship between state and national anti-smoking media campaigns and cessation behaviors among adult smokers in the U.S. Design: Repeated cross-sectional analysis. Setting: U.S. nationally representative survey of adults ages 18 and older, 2001-2015. Subjects: 76, 278 year-ago smokers from the 2001-2015 Tobacco Use Supplement to the Current Population Survey. Measures: Area-level exposure to State-sponsored and "Tips from former smokers" anti-tobacco media campaigns was the primary predictor of this study. Outcome variables included: quit attempt in the past 12 months, past 30-day smoking cessation, and past 90-day smoking cessation among year-ago smokers. Analysis: We conducted modified Poisson regression models to examine the association between media campaign exposure and cessation behaviors. We also examined effect modification on the additive scale by sex, race/ethnicity, income, and education using average marginal effects. Results: Year-ago smokers with greater exposure to media campaigns were more likely to report 30-day (Prevalence Ratio [PR]: 1.18, CI: 1.03, 1.36) and 90-day cessation (PR: 1.18, CI: 1.00, 1.41) compared to respondents with less campaign exposure. We found no evidence of effect modification by sociodemographic variables. Conclusion: Exposure to anti-smoking media campaigns were associated with year-ago smokers' cessation behaviors. However, there were no differences in the association by sex, race/ethnicity, income, or education, indicating that broadly focused media campaigns may be insufficient to reduce smoking cessation among priority populations, and thus health disparities generally.